2022
DOI: 10.1002/anie.202206157
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Multilevel Stimuli‐Responsiveness and Multicolor Room‐Temperature Phosphorescence Emission Based on a Single‐Component System

Abstract: There are limited reports about the transformation of pure organic room-temperature phosphorescence (RTP) materials with multilevel stimuli-responsiveness at different RTP emission wavelengths under external stimuli. It is difficult to ensure efficient intersystem crossing (ISC) in different states of a singlecomponent system. This research reports the conversion of the organic single-component small molecule 1,2bis(4-alkoxyphenyl)ethane-1,2-dione (N-BOX) with multilevel stimuli-responsiveness between high-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 72 publications
1
70
0
2
Order By: Relevance
“…1 H NMR (600 MHz, DMSO-d 6 , 298 K, δ): 10.71 (s, 1H), 8.95 (d, J = 8.6 Hz, 1H), 8.45 (d, J = 7.2 Hz, 1H), 8.11 (s, 1H), 8.06 (t, J = 7.8 Hz, 1H), 7.88 (t, J = 7.9 Hz, 1H), 7.81 (d, J = 6.1 Hz, 1H), 7.76 (d, J = 8.6 Hz, 1H), 7.19-7.15 (m, 5H), 7.10 (t, J = 7.2 Hz, 2H), 7.05 (d, J = 7.5 Hz, 4H), 3.97 (t, J = 7.2 Hz 2H), 1.59-1.54 (m, 2H), 1.35-1.28 (m, 2H), 0.90 (t, J = 7.4 Hz, 3H). 13 C NMR (151 MHz, DMSO-d 6 , 298 K, δ): 164. 16, 163.83, 150.63, 143.62, 141.90, 139.12, 138.21, 133.78, 130.12, 128.01, 127.86, 127.74, 126.33, 125.79, 122.66, 119.59, 117.56, 115.81, 115.37, 55.37, 30.21, 20.30, 14.16 Construction of Mild-Stimuli-Responsive Fluorescent Molecular Systems: Two kinds of mild-stimuli-responsive fluorescent systems were constructed in solution and film state of the NI-CBN, respectively.…”
Section: Synthesis Of Ni-cbnmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR (600 MHz, DMSO-d 6 , 298 K, δ): 10.71 (s, 1H), 8.95 (d, J = 8.6 Hz, 1H), 8.45 (d, J = 7.2 Hz, 1H), 8.11 (s, 1H), 8.06 (t, J = 7.8 Hz, 1H), 7.88 (t, J = 7.9 Hz, 1H), 7.81 (d, J = 6.1 Hz, 1H), 7.76 (d, J = 8.6 Hz, 1H), 7.19-7.15 (m, 5H), 7.10 (t, J = 7.2 Hz, 2H), 7.05 (d, J = 7.5 Hz, 4H), 3.97 (t, J = 7.2 Hz 2H), 1.59-1.54 (m, 2H), 1.35-1.28 (m, 2H), 0.90 (t, J = 7.4 Hz, 3H). 13 C NMR (151 MHz, DMSO-d 6 , 298 K, δ): 164. 16, 163.83, 150.63, 143.62, 141.90, 139.12, 138.21, 133.78, 130.12, 128.01, 127.86, 127.74, 126.33, 125.79, 122.66, 119.59, 117.56, 115.81, 115.37, 55.37, 30.21, 20.30, 14.16 Construction of Mild-Stimuli-Responsive Fluorescent Molecular Systems: Two kinds of mild-stimuli-responsive fluorescent systems were constructed in solution and film state of the NI-CBN, respectively.…”
Section: Synthesis Of Ni-cbnmentioning
confidence: 99%
“…Over the last few decades, organic luminescent materials with responses to one or more external “triggers,” such as light, [ 11,12 ] heat, [ 13,14 ] mechanical force [ 15,16 ] and chemical vapors, [ 17,18 ] have gained increasing attention owing to their potentials for a variety of applications. [ 19 ] The feature of adjustable fluorescence color changes on demand endows the smart materials with an encoding capacity, as well as an easily decodable property through visualized patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase conversion from the crystalline to the amorphous states is one of the most common transformations that occur as a result of mechano-responsive fluorescent compounds being subjected to a mechanical stimulus. [74][75][76][77] The said transformation contributed to MCL accompanied by structural variation of solvent exclusion, intermolecular interactions transformation, conformational fluctuations, and so on.…”
Section: Induced By the Crystalline-to-amorphous Phase Transitionmentioning
confidence: 99%
“…Organic room temperature phosphorescence (RTP) materials with a long afterglow property have unique advantages in anticounterfeiting, biological diagnosis and treatment, and optoelectronic devices. Intersystem crossing (ISC) of excitons and stable triplet excitons are prerequisites for organic materials to exhibit phosphorescence. Early organic RTP materials were mainly single-component compounds; the researchers increased the ISC ability of excitons by introducing carbonyl groups or halogen atoms into the molecules or designing donor–acceptor type molecular configurations. , As an emerging technology in recent years, people have found that guest–host doped strategy can cause the doped materials to have RTP activity, which has attracted widespread attention. The host matrix can help the energy transfer of guest excitons, and the rigid structure of the host can effectively limit the motion of the guests, thereby stabilizing the triplet excitons. However, despite the rapid development of doped RTP materials, these systems are basically two-component systems, which are often limited by low performance and limited functionality.…”
mentioning
confidence: 99%